Alaska Victimization Survey: Intimate Partner and Sexual Violence in the Ketchikan Gateway Borough - Morton, Lauree; Rosay, André B.; Myrstol, Brad A.; Rivera, Marny (Justice Center, University of Alaska Anchorage; Council on Domestic Violence and Sexual Assault, Alaska Department of Public Safety, 2013)
This Powerpoint slide presentation presents an overview of key results from the 2012 Alaska Victimization Survey for the Ketchikan Gateway Borough, which was conducted from April to July 2013, and results were released on October 15, 2013 in Ketchikan. Findings include: * 50% of adult women in the Ketchikan Gateway Borough have experienced intimate partner violence, sexual violence or both, in their lifetime; * 9% have experienced intimate partner violence, sexual violence or both, in the past year; * More than 3 out of every 10 adult women in the Ketchikan Gateway Borough have experienced sexual violence in their lifetime; and * More than 4 out of every 10 have experienced intimate partner violence in their lifetime. Council on Domestic Violence and Sexual Assault, Alaska Department of Public Safety Alaska Victimization Survey in Ketchikan / Intimate Partner Violence Definitions / Intimate Partner Violence Estimates / Sexual Violence Definitions / Sexual Violence Estimates / Summary of Past Year Estimates / Summary of Lifetime Estimates / Lifetime Estimates / Important Limitations / A Special Thank You! / Contacts